Sox11 Modified Tendon-Derived Stem Cells Promote the Repair of Osteonecrosis of Femoral Head. (26th October 2021) - Ni, Ming; Sun, Weiwei; Li, Yucong; Ding, Lingli; Lin, Weiping; Peng, Haiwen; Zheng, Qingyuan; Sun, Jingyang; Li, Juncheng; Liu, Hao; Yang, Yi; Xu, Liangliang; et al.
Osteonecrosis of the femoral head (ONFH) is a leading cause of mobility impairment which may lead to a total hip replacement. Recent studies have found tendon derived stem cells (TDSCs) might be an ideal cell source for musculoskeletal tissue regeneration. And our previous study has shown Sox11 could promote osteogenesis of bone marrow-derived MSCs. However, the effect of TDSCs or Sox11 over-expressing TDSCs (TDSCs-Sox11) on bone regeneration in ONFH has not been investigated. In the present study, TDSCs were infected with AAV carrying Sox11 or empty vector. We showed that Sox11 could promote the proliferation and osteogenic differentiation of TDSCs, as well as angiogenesis in vitro. The western blot analysis showed that Sox11 could activate the PI3K/Akt signaling pathway to promote osteogenesis of TDSCs. Finally, using a rabbit model of hormone-induced ONFH, our result demonstrated that local administration of TDSCs or TDSCs overexpressing Sox11 could accelerate bone regeneration in necrotic femoral heads, and TDSCs overexpressing Sox11 showed better effects. TDSCs over-expressing Sox11 might be a promising cell source for stem cell therapy to promote bone regeneration, such as ONFH, fracture, bone defect, and so on.